Penyebab Kecemasan Matematika Mahasiswa Calon Guru Asal Papua - Alberta Parinters Makur; Rully Charitas Indra Prahmana (Universitas Hamzanwadi, 2015)
An increasing number of Papuans qualified teachers realized by sending young people from Papua to continue their education in the College of Education. But the basic capabilities, especially mathematics, which owned high school students graduated from Papua that continuing education is very low. This, presumably because the students have math anxiety, thus preventing them from material master mathematics. By using a qualitative research approach, particularly the case study method, this research describes what factors are the cause of math anxiety prospective teacher students from Papua, based on the results of questionnaires and interviews that have been analyzed.